-5(x+4)+3x+5=5x+12

Simple and best practice solution for -5(x+4)+3x+5=5x+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x+4)+3x+5=5x+12 equation:


Simplifying
-5(x + 4) + 3x + 5 = 5x + 12

Reorder the terms:
-5(4 + x) + 3x + 5 = 5x + 12
(4 * -5 + x * -5) + 3x + 5 = 5x + 12
(-20 + -5x) + 3x + 5 = 5x + 12

Reorder the terms:
-20 + 5 + -5x + 3x = 5x + 12

Combine like terms: -20 + 5 = -15
-15 + -5x + 3x = 5x + 12

Combine like terms: -5x + 3x = -2x
-15 + -2x = 5x + 12

Reorder the terms:
-15 + -2x = 12 + 5x

Solving
-15 + -2x = 12 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-15 + -2x + -5x = 12 + 5x + -5x

Combine like terms: -2x + -5x = -7x
-15 + -7x = 12 + 5x + -5x

Combine like terms: 5x + -5x = 0
-15 + -7x = 12 + 0
-15 + -7x = 12

Add '15' to each side of the equation.
-15 + 15 + -7x = 12 + 15

Combine like terms: -15 + 15 = 0
0 + -7x = 12 + 15
-7x = 12 + 15

Combine like terms: 12 + 15 = 27
-7x = 27

Divide each side by '-7'.
x = -3.857142857

Simplifying
x = -3.857142857

See similar equations:

| -7(x+3)+3x+7=5x+11 | | ((d-4)/(4))^(2)=64 | | 1/3*6h=20 | | -3(2x+5)=7x+1 | | 7(x-7)+2=9-(x+6) | | 3(x-3)=2-8x | | x-3=.75(2-x)+6 | | 2h-3h=15 | | X/0.4=11.25 | | 11x^2=44x | | 5x/x=(8x^3)/x^2 | | Y-4=-8.4 | | lnx^2+3x-1=0 | | -(-2n-5)=-13-n | | 2(3*-4)=22 | | x11/20*30 | | x=11/30x230 | | 4k-5=6k+1 | | 5(m-4)=2m+3 | | -2(z-11/5)=3z | | 2x^2-6x-9=89 | | 18=-8x+6x | | 7+6x+6x=47 | | 4x^2-16x-33=0 | | 5/6x-7/8=1/6x-1/4 | | 3/2x-(3-4x)=1/3 | | 3(3)+2(5)=60x-500 | | 5+14a=9x-5 | | 2/3×-11=14 | | -.12x^2+2.4x=8 | | y=7sinx-4 | | (x-1/3x)^2 |

Equations solver categories